2010
DOI: 10.2514/atcq.18.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Intent Error’s Impact on Aircraft Prediction

Abstract: Unprecedented global initiatives have begun to redesign the aviation systems that provide for the efficient and safe transport of civilian aircraft. Success of these initiatives is only possible through global collaborations that allow broader analyses and data to be shared. The paper reports on just such a study that examines the lateral deviations from the automation's known horizontal route of flight to the actual aircraft position. These errors are due to the typical navigation and surveillance errors, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The near-term goal of the trajectory downlink is to correct for errors in flight plan trajectory information due to tactical maneuvering of the aircraft for separation assurance or weather deviations, but the trajectory downlink may potentially support TBO's needs for trajectory communication and negotiation. Controllers today are not incentivized to consistently update flight plans to account for tactical maneuvering of the aircraft for separation assurance or weather, and FAA studies have shown that lateral errors of 20 to 30 NM are common in the NAS and in Europe, and that these lateral errors in intent information result in poor performance of conflict detection tools 7 .…”
Section: Trajectory Data and Formatmentioning
confidence: 99%
“…The near-term goal of the trajectory downlink is to correct for errors in flight plan trajectory information due to tactical maneuvering of the aircraft for separation assurance or weather deviations, but the trajectory downlink may potentially support TBO's needs for trajectory communication and negotiation. Controllers today are not incentivized to consistently update flight plans to account for tactical maneuvering of the aircraft for separation assurance or weather, and FAA studies have shown that lateral errors of 20 to 30 NM are common in the NAS and in Europe, and that these lateral errors in intent information result in poor performance of conflict detection tools 7 .…”
Section: Trajectory Data and Formatmentioning
confidence: 99%
“…Specifically, the authors are detecting and resolving conflicts at greater than the legal standard for separation of five nmi horizontally and 1,000 ft vertically using a geometric conflict detection scheme. While improving trajectory prediction accuracy is beneficial for detecting conflicts when using automated conflict probes, 2,3,4,5 and validating the accuracy of a trajectory prediction is seen as a necessary part of the future National Airspace System 6 (NAS), improving trajectory prediction performance often requires some form of equipage on the aircraft and/or data sharing, which can make the solution more difficult and expensive to implement in actual operations. There are alternative approaches that try to use adaptive algorithms to improve the accuracy of trajectory predictions, particularly during climb, by adapting either the modeled aircraft thrust 7,8 or weight.…”
Section: Introductionmentioning
confidence: 99%
“…Ground-based trajectory predictors (TPs) often lack critical information required to predict an aircraft's future trajectory [2], or the information is not up to date due to clearances issued by air traffic control (ATC) that have not been entered into the ground-based system [3].…”
Section: Introductionmentioning
confidence: 99%